LKPD IPA Berbasis Inquiry Terbimbing Terintegrasi Nilai Islam untuk meningkatkan Hasil Belajar Kognitif di MTS Negeri 1 Halmahera Timur - Firjan Hi Sabtu; Ade Haerullah; Said Hasan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aimed to determine the influence of the use of Science Student Worksheets (LKPD) based on Guided Inquiry integrated Islamic values ​​on cognitive learning outcomes at MTs Negeri 1 East Halmahera. This type of research uses experimental research (pseudo) which follows the form of a Non-equivalent Control Group Design Pretest and posttest. The sample selection used a purposive sampling technique. The research was carried out in 2 classes, namely the experimental class using guided inquiry-based science worksheets integrated with Islamic values ​​and the control class, namely the guided inquiry model. The research instrument uses an essay test question assessment sheet. Data analysis used parametric tests and hypothesis testing using the Anacova test in the SPSS-assisted Tests of Between-Subjects Effects. The results showed that there was an effect of the use of Science Student Worksheets (LKPD) based on Guided Inquiry integrated with Islamic values ​​on cognitive learning outcomes at MTs Negeri 1 Halmahera Timur with a significant level of 0.23.